Indonesian Culturally-Bound Words Translation in the Legends into English - Tursini, Umi; Jelita, Nanda Pratiwi Cahya (Rhizome : Jurnal Kajian Ilmu Humaniora, 2023)
The aim of this research is to find out the culturally-bound words found in the legends and how the culturaly-bound words in legends are translated into English. Three legends entitled Lutung Kasarung, Timun Mas, and Keong Mas are analyzed qualitatively by using the culturally-bound words categories and translation strategies by Newmark (1988).The results show that there are 23 words included culturally-bound words which are separated into four categories and was translated by using six strategies by Newmark (1988). The four categories namely ecology; material culture; organisation, custom, activities; and gesture and habit. The six strategies by Newmark (1988) were cultural equivalent, functional equivalent, descriptive equivalent, modulation, transference, and synonymy. The findings provide reference to understand the Indonesian culturally-bound words and how they are translated into English.